Profiling Botswana consumers of furniture, appliances and electronics : demographics, lifestyle, values, shopping motivation, product-attitudes and information sources - Smit, Henrietta Augusta (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.